Huantinamarca. Analysis of the management of the archeological site. San José S.A.C case-study (Lima, Peru) - Aldaba Flores, Karina (2018)
The archaeological site of Huantinamarca is located in the district of San Miguel, in Lima (province and state), Peru. After almost 50 years of being an ornamental component in the Pacific International Fair, it became part of the real estate project Parques de la Huaca, promoted by San José S.A.C. Through such a project, there existed the goal of making the pre-Hispanic building come closer to the community. This was to be done raising, in its surroundings, modern and utilitarian spaces, such as buildings and a public park. The main objective of the intervention was to achieve the visual and affective integration of the monument into the daily life of the occupants of the Parques de la Huaca housing complex, after the research work, conservation, restoration and landscape treatment for its preservation had occurred. Currently, those who live in front of the huaca are unaware of its cultural value. The municipality does not have a land use planning program for the protection of the different huacas in its jurisdiction. Urban growth evidences an inadequate policy of local cultural management. This document proposes urban reconversion and the promotion of better citizen education as strategic components of cultural management for the preservation and revaluation of cultural and natural heritage, such as Huantinamarca in San Miguel.